Fatigue crack growth behaviour of selective laser-melted 18NI300 manufactured at 0º, 45º and 90º to perpendicular crack growth plane - Moreno Cerezo, Pablo; Aguilera-García, José Antonio; García-González, Antonio Luis; Moore, Steven; Wheatley, Greg; López-Crespo, Pablo (My University, 2023)
The use of selective laser melting (SLM) as a method of additive manufacturing (AM) of valuable objects has a promising future. Maraging steel is a widely used material due to its excellent qualities in AM, so it is essential to know the fatigue mechanisms existing in this material manufactured at different angles. The current state of research in fracture mechanics applied to additive manufacturing has been analyzed to determine the importance of mechanical properties in this process. The CT samples were laser fabricated in three orientations with respect to the intended crack plane; the angles used are 0-, 45- and 90-degrees respect from the displacement. Fatigue tests show a longer service life with the 90-degree specimens than with the 0-degree specimens, with a reduction up to 20% for the 0-degree tests. On the 45-degree specimens, a 40% reduction is observed compared to the 90-degree specimens, and there is no apparent reason. A fracture surface analysis has shown different textures on the 45-degree specimens, with rougher surfaces in certain tests due to a rougher application of load. This also results in sharper ridges signifying rapid cracking due to shorter periods of higher forces. In addition, it is necessary to continue the study to obtain the da/dN curves, as well, the reasons for these difference in surface areas.
Keywords: Ciencia de los materiales - Congresos; Additive Manufacturing (AM); Fatigue; Fracture mechanism; Maraging steel; Selective laser melting (SLM)